Long-term underwater images from around a single mooring site in McMurdo Sound, Antarctica (2017-2019) - Cziko, Paul (IEDA: US Antarctic Program Data Center, 2020)
Long-term images taken by the camera from the McMurdo Oceanographic Observatory mooring in McMurdo Sound, Antarctica during its 2-year deployment (2017-2019). The mooring was situated at the seawater terminus of the McMurdo Station seawater intake jetty at 21 m deep, typically under thick sea ice cover. The automated 360° pan-tilt-zoom (ptz) camera, inside of an air-filled self-cleaning dome, was programmed to move to 42 ptz \"waypoints\" every hour and take a still 1920x1080 JPG image for archiving. Lights, oriented in one direction only, illuminated a rock/rubble slope for much of each winter, when there was no natural illumination. The camera was situated on a concrete block, which elevated the camera about 1m off of the seabed. Motile and sessile benthic biota, including notothenioid fishes, anemones, pycnogonids, asteroids, soft-corals, sponges, and nudibranchs are commonly seen in the images. Some ptz waypoints survey the water column and underside of the sea ice, capturing also the presence of larval/juvenile fishes and other plankton/nekton in the water column. Maximum intervals between subsequent images from the same ptz waypoint were about 1 hour, though many waypoints were captured at somewhat higher frequency. Interval images, taken at 5-min intervals irrespective of camera orientation, were also captured. Images are occasionally obscured/impacted by the camera dome's wiper, darkness, low visibility, minor fouling of the camera dome, and out-of-focus lens elements.